Purification and properties of 6-methylsalicylic acid synthase from Penicillium patulum. - Spencer, J B (1992)
6-Methylsalicylic acid synthase has been isolated in homogeneous form from Penicillium patulum grown in liquid culture from a spore inoculum. The enzyme is highly susceptible to proteolytic degradation in vivo and in vitro, but may be stabilized during purification by incorporating proteinase inhibitors in the buffers. The enzyme exists as a homotetramer of M(r) 750,000, with a subunit M(r) of 180,000. 6-Methylsalicyclic acid synthase also accepts acetoacetyl-CoA as an alternative starter molecule to acetyl-CoA. The enzyme also catalyses the formation of small amounts of triacetic acid lactone as an oligatory by-product of the reaction. In the absence of NADPH, triacetic acid lactone is the exclusive enzymic product, being formed at 10% of the rate of 6-methylsalicylic acid. The enzyme is inactivated by 1,3-dibromopropan-2-one, leading to the formation of cross-linked dimers similar to that observed with type I fatty acid synthases. Acetyl-CoA protects the enzyme against the inactivation and inhibits dimer formation. An adaptation of the purification method for 6-methylsalicylic acid synthase may be used for the isolation of fatty acid sythase from Penicillium patulum.